Effect of the Synthesis Method of MgAl2O4 and of Sn and Pb Addition to Platinum Catalysts on the Behavior in n-Butane Dehydrogenation - Bocanegra, Sonia Alejandra (2010)
The MgAl2O4 spinels, synthesized by using two different methods (ceramic and coprecipitation), show very low acidity and good dispersion capacity of the metallic phase, these properties being suitable for the use of these materials as supports. However, MgAl2O4 cer displays higher strong acidity than MgAl2O4 cop which seems to influence the metal-support interaction, since Pt/MgAl2O4 cer catalyst shows higher metallic dispersion, lower metal particle sizes, and better catalytic behavior than the Pt/MgAl2O4 cop one. The Sn addition to Pt/ MgAl2O4 improves the performance in the n-butane dehydrogenation process, increasing the activity, stability, and selectivity to butenes. This behavior is due to the presence of important Pt-Sn interactions, mainly in bimetallic catalysts supported on MgAl2O4 cer. On the other hand, the Pb addition to monometallic catalysts does not enhance the catalytic performance in dehydrogenation. This behavior is in agreement with the characterization results of metallic phase that indicate important blocking effects in PtPb/MgAl2O4 cer catalysts, and segregation effects in PtPb/MgAl2O4 cop. In conclusion, the ceramic method of MgAl2O4 preparation provides the best support for PtSn catalysts in n-butane dehydrogenation reaction.